DEVELOPMENT OF PROPOSALS TO IMPROVE THE ACTIVE MODEL OF SELECTING LABOR RESOURCES TO ADMINISTRATION OF MUNICIPAL EDUCATION (Вестник университета)
A set of measures and methodological recommendations for improving the model of the selection of labor resources in the administration of the municipal formation by the example of the urban settlement of Kamenka in the Penza region of the Russian Federation has been developed. The most important element in improving the quality of municipal employees is the integration into their activities of the latest achievements of digital technologies. Digital technologies that are advisable to introduce into the activities of municipal employees are represented mainly by modern software that optimizes efforts and enhances the transparency of their activities. It is shown that the introduction of the electronic system in the model of recruitment of labor resources to the administration of the municipal formation minimizes the subjective factor in the selection of labor resources and maximizes the effect of the conducted activities.